Decreased brain functional connectivity associated with cognitive dysfunction in women with second pregnancy - Zhang, Juan; Zhang, Tao; Chen, Yu-Chen; Chen, Huiyou; Feng, Yuan; Tang, Wen-Wei; Zheng, Jin-Xia (Frontiers in Aging Neuroscience, 2022)
Purpose: Previous research has found that women with second pregnancy may have an increased risk of cognitive dysfunction. This study aims to investigate the intrinsic functional connectivity (FC) pattern of the DMN anchored on posterior cingulate cortex (PCC) in postpartum women, especially the parous women using resting-state functional magnetic resonance imaging (rs-fMRI). Methods: Twenty parous women, 26 primiparous women, and 30 nulliparous women were included for rs-fMRI scan. They were age and education well matched. A seed based FC method was conducted to reveal FC patterns with other brain regions using a region of interest in the PCC. The relationships between FC patterns and cognitive performance were further detected. Results: Relative to primiparous women, parous women had significantly decreased FC primarily between the PCC and the right middle frontal gyrus and right parahippocampal gyrus. The decreased FC to the right parahippocampal gyrus in parous women was positively associated with the reduced DST scores (rho=0.524, p=0.031). Moreover, parous women compared with nulliparous women showed significantly decreased FC between the PCC and the left superior frontal gyrus and left middle frontal gyrus. The reduced FC to the left superior frontal gyrus in parous women was also positively associated with the lower DST scores (rho=0.550, p=0.022). Conclusion: Our result highlights that women with second pregnancy revealed decreased FC between the DMN regions with the parahippocampal gyrus and prefrontal cortex, which was correlated with specific impaired cognitive function. This study may provide new insights into the neuropathological mechanisms of postpartum cognitive impairment and enhance our understanding of the neurobiological aspects during postpartum period.